Significance of character ‘H’ in soundex patterns on Indian Names - Jaisunder, G C; Dr Israr Ahmad,; Dr Dhavamani Christober, (IJRDO -Journal of Computer Science Engineering, 2021)
In this digitization age, particularly under the umbrella of Digital India scheme, each and every establishment in India is in the process of digital transformation one way or the other. The establishments vary from small private business to larger enterprise and in the government sector in various levels of central/ state/ district administration. In government, the enrollment, verification, identification, usage and maintenance of demographic data particularly on the personal names in the critical government records play a very important role.  A very small spelling mistake in the name at the time of enrollment process leads to complications and the citizen runs from pillar to post for the rectification process. Though the rectification process in every system of enrollment is well defined, the process to get the spelling mistake corrected is very painful. The applicant needs to defend himself with ‘n’ number of documents available with him to prove his correct spelling in the required document. In recent years, the spelling mistakes happening at the enrollment stage are being resolved at the initial stage itself as the data entry is in the form of self service. One of the best practices is to get the consent of the applicant directly prior to processing his/ her application. The complication starts when the enrollment process happens in the absence of the applicant as the consent of the concerned applicant can’t be taken across the counter. In government, most of the citizenship services are outsourced and the data correction process is being carried out as a separate entity as part of the application acceptance. During the application acceptance process, every agency does the data verification in their own style as per the guidelines from the concerned government. Irrespective of the methodology being followed in name checking, the earlier occurrence of the same applicant within their own system is being carried out as part of the verification process. To implement this activity, government agencies need to follow some sort of soundex mechanism to find out the alternatives over the names in the data base and cross verify the same with other related parameters. In this scenario, it is understood that the spelling of the same name in a different part of India differs phonetically as some characters play a significant role.  In this paper, we have tried to find and analyze the significance of the character ‘H’ in soundex patterns in Indian names.